What is the optimal caesarean section rate? An outcome based study of existing variation. Issue 4 (August 1994) - Joffe, M; Chapple, J; Paterson, C; Beard, R W
Abstract : STUDY OBJECTIVE–To investigate the consequences of different levels of caesarean section (CS) rate in terms of fetal and maternal outcomes. DESIGN–Comparison of outcome variables between four categories of maternity units stratified according to CS rates. Data were collected concurrently. SETTINGS–All 17 maternity units in one health region. SUBJECTS–Data for the perinatal mortality analysis: all 221, 867 deliveries in 1983-87 (excluding severe malformations) (1462 deaths); maternity information analysis system: all 36, 727 women with singleton pregnancies who delivered in 1988. OUTCOME MEASURES–Perinatal mortality, Apgar scores at one and five minutes, onset of respiration after one minute, postnatal transfusion, postnatal infection, thromboembolism, low haemoglobin concentration at discharge, and puerperal psychosis were determined. RESULTS–Teaching hospitals with an increased proportion of high risk cases had the highest CS rate, but the other three categories were found to serve comparable populations. Perinatal mortality showed a birthweight specific pattern–for very low birthweight infants, but not for other deliveries, mortality rates were lower in units with higher CS rates. Apgar scores showed no trend, but the onset of respiration after one minute was significantly more frequent in units with a CS rate of less than 10%. Increased maternal postnatal blood transfusion was associated with higher CS rates but no trend was observed for the other maternal variables. CONCLUSIONS–CS rates in general maternity units should be 10 to 12% or lower in the singleton population as a whole, but a more interventionist approach is indicated for very low birthweight infants. If confirmed, these recommendations could easily be incorporated into clinical audit.